Potensi Dedak Padi yang Difermentasi dengan Enzim Fitase dalam Pakan Basal Terhadap Kolesterol Total Darah Ayam Petelur - Nurfitri, Yulia; Lamid, Mirni; Yuliani, Margareth Gandul Atik; Al-Arief, Mohamad Anam; Wahyuni, Retno Sri; Aksono, Eduardus Bimo (Journal of Basic Medical Veterinary, 2020)
This study aimed to evaluate the potential of rice bran fermented by the enzyme phytase in basal feed to the total blood cholesterol level of laying hen. This research use an experimental method in vivo with a completely randomized design consisting of six treatments and four replications in each treatment. The experimental animals used 24 48-week-old female laying hen strain Isa Brown. The treatment wa given basal feed substituted with different percentage of fermented rice bran by phytase enzyme and 2% lemuru fish oil supplementation. In this research the amount of fermented rice bran by phytase enzyme substituted on basal feed was: treatment P0 (-) (0%), P0 (+) (0%), P1 (5%), P2 (10%) P3 (15%) and P4 (20%). The results of the statistical analysis showed that there are no significant differences (p> 0.05) on total blood cholesterol levels in all treatments. The conclusion of the research is that rice bran fermented by phytase enzymes tends to decrease total blood cholesterol levels in laying hen.